Evaluasi Kebijakan Pemerintah dalam Ketahanan Pangan - Hutahaean, Rosa; Dompak, Timbul (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This study aims to examine the policies implemented by the Batam City Government in responding to food security in the city. The research method used is descriptive and qualitative for the study. The results of the study identified sub-districts such as Batu Legong, Temoyong, and Bulang Lintang as the main priorities that require serious attention from the government. Food facilities and infrastructure in these sub-districts need to be strengthened through adequate allocation of resources and budgets. The audience, as key stakeholders, play a crucial role in implementing these recommendations. In addition, an in-depth evaluation also needs to be carried out on the condition of food infrastructure in sub-districts with lower levels of vulnerability. Sustainable food assistance programs and collaboration with the private sector and civil society are strategic steps in improving overall food security. Nutrition counseling and education to the community are also important to improve understanding of healthy eating patterns. The conclusion is that 33 sub-districts in Batam City still lack facilities and infrastructure to provide food. Keywords: Indicators, Food Security Concept, Public Policy